2015
DOI: 10.1007/s10840-015-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

A peptidomimetic inhibitor suppresses the inducibility of β1-adrenergic autoantibody-mediated cardiac arrhythmias in the rabbit

Abstract: Purpose Previous studies demonstrated that burst pacing and subthreshold infusion of acetylcholine in β1-adrenergic receptor (β1AR)-immunized rabbits induced sustained sinus tachycardia. The aim of this study was to examine the anti-arrhythmogenic effect of a newly designed retro-inverso (RI) peptidomimetic inhibitor that specifically targets the β1AR antibodies in the rabbit. Methods Six New Zealand white rabbits were immunized with a β1AR second extracellular loop peptide to produce sympathomimetic β1AR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Li et al demonstrated that expression of sympathomimetic β-AR-activating antibodies in rabbit model led to a significant reduction of atrial ERP. 23 Stavrakis et al have shown that seropositivity for anti-β1-R differed significantly between patients with AF and sinus rhythm in Graves' hyperthyroidism (94% vs 38%, P < 0.001). In a small study, anti-β1-R positivity was detected in 41.6% of patients with AF and 10% of patients in the healthy control group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Li et al demonstrated that expression of sympathomimetic β-AR-activating antibodies in rabbit model led to a significant reduction of atrial ERP. 23 Stavrakis et al have shown that seropositivity for anti-β1-R differed significantly between patients with AF and sinus rhythm in Graves' hyperthyroidism (94% vs 38%, P < 0.001). In a small study, anti-β1-R positivity was detected in 41.6% of patients with AF and 10% of patients in the healthy control group.…”
Section: Discussionmentioning
confidence: 97%
“…Li et al. demonstrated that expression of sympathomimetic β‐AR‐activating antibodies in rabbit model led to a significant reduction of atrial ERP . Stavrakis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen male New Zealand white rabbits (each weighing 3.0-3.5 kg at baseline) were obtained from the Experimental Animal Center of Xinjiang Medical University (Urumqi, China) and were randomly divided into two groups: a control group and an immune group. The generation of the animal model followed the protocols of previous studies (Li et al, 2014(Li et al, , 2015(Li et al, , 2016, and a flow chart of the experimental design is shown in Figure 1A. The immune group was initially FIGURE 1 | Schematic of the study process.…”
Section: Experimental Animals and Designmentioning
confidence: 99%
“…Rabbits in the control group received an equal amount of adjuvant without the β1AR ECL2 peptide at the same time points. Blood samples were collected from both groups every 2 weeks in an awake state before injection, and the serum β1ARAb levels were measures by ELISA and expressed as optical density values based on previous studies (Li et al, 2015). Transthoracic echocardiographic examination was performed at baseline and repeated at 8 weeks after the first immunization.…”
Section: Experimental Animals and Designmentioning
confidence: 99%
See 1 more Smart Citation